The Funambulist Papers, Volume 1 - Lambert, Leopold, 1985- (Book collections on Project MUSE., 2020)
This book is a collection of thirty-five texts from the first series of guest writers' essays, written specifically for The Funambulist weblog from June 2011 to November 2012. The idea of complementing Lambert's own texts on his blog with those written by others originated from the idea that having friends communicate with each other about their work could help develop mutual interests and provide a platform to address an audience. Thirty-nine authors of twenty-three nationalities were given the opportunity to write essays about a part of their work that might fit with the blog's editorial line. Overall, two 'families' of texts emerged, collected in two distinct parts in this volume. The first one, The Power of the Line, explores the legal, geographical and historical politics of various places of the world. The second, Architectural Narratives, approaches architecture in a mix of things that were once called philosophy, literature and art. This dichotomy represents the blog's editorial line and can be reconciled by the obsession of approaching architecture without care for the limits of a given discipline. This method, rather than adopting the contemporary architect's syndrome that consists in talking about everything but being an expert in nothing, attempts to consider architecture as something embedded within (geo)political, cultural, social, historical, biological, and dromological mechanisms that widely exceed what is traditionally understood as the limits of its expertise.